2015
DOI: 10.1155/2015/381931
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Atherosclerosis in Egyptian Rheumatoid Arthritis Patients and Its Relation to Disease Activity

Abstract: Aim. To detect the frequency of subclinical atherosclerosis in rheumatoid arthritis patients without clinically evident atherosclerosis and to correlate its presence with the disease activity. Patients and Methods. Our study includes 112 RA patients (group 1) and 40 healthy controls (group 11). All patients and controls were subjected to full history taking, clinical examination, and laboratory investigations. Carotid intima media wall thickness (IMT) and carotid plaques were measured in both groups by B-mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(33 reference statements)
4
3
1
Order By: Relevance
“…Our results are similar to those of Dionicio et al reported in 2012 [45]. In contrast, Rawhya et al reported only an association with disease activity [46].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are similar to those of Dionicio et al reported in 2012 [45]. In contrast, Rawhya et al reported only an association with disease activity [46].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, There was high significant association between presence of atherosclerosis and RF with mean (226.28±42.58), (p < 0.001) in contradictory with Elshereef et al [23] who didn't report association between RF and subclinical atherosclerosis (P<0.5) as compare between 77 RA patient with atherosclerosis and 35 RA patients without atherosclerosis.…”
Section: Discussioncontrasting
confidence: 91%
“…In this study there was no correlation between DAS28 score of RA patients versus endothelial dependent flow mediated dilatation (FMD) % of the brachial artery, (r= -0.282, P=0.047). Similar results were found by Elshereef et al [23] where FMD dilatation percent and dilatation ratio were ( = 0.005, = 0.007, resp.) in RA patients.…”
Section: Discussionsupporting
confidence: 90%
“…Endothelial dysfunction, carotid intima-media thickness and plaque evaluations provide an accurate detection of the atherosclerotic process at a preclinical stage, before the appearance of clinical disease, allowing preventive measures to decrease cardiovascular risk in subjects with RA [46,47]. Arterial stiffness, as a preclinical marker of atherosclerosis, is a predictive factor of cardiovascular disease [48,49].…”
Section: Discussionmentioning
confidence: 99%